Modelling the relationship between 231Pa/230Th distribution in North Atlantic sediment and Atlantic Meridional Overturning Circulation - Siddal, Mark; Stocker, Thomas F.; Henderson, Gideon M.; Joos, Fortunat; Frank, Martin; Edwards, Neil R.; Ritz, Stefan; Müller, S. A. (Paleoceanography, 2007)
Down-core variations in North Atlantic 231Paxs/230Thxs have been interpreted as changes in the strength of the Atlantic meridional overturning circulation (AMOC). This modeling study confirms that hypothetical changes in the AMOC would indeed be recorded as changes in the distribution of sedimentary 231Paxs/230Thxs. At different sites in the North Atlantic the changes in sedimentary 231Pa/230Th that we simulate are diverse and do not reflect a simple tendency for 231Paxs/230Thxs to increase toward the production ratio (0.093) when the AMOC strength reduces but instead are moderated by the particle flux. In its collapsed or reduced state the AMOC does not remove 231Pa from the North Atlantic: Instead, 231Pa is scavenged to the North Atlantic sediment in areas of high particle flux. In this way the North Atlantic 231Paxs/230Thxs during AMOC shutdown follows the same pattern as 231Paxs/230Thxs in modern ocean basins with reduced rates of meridional overturning (i.e., Pacific or Indian oceans). We suggest that mapping the spatial distribution of 231Paxs/230Thxs across several key points in the North Atlantic is an achievable and practical qualitative indicator of the AMOC strength in the short term. Our results indicate that additional North Atlantic sites where down-core observations of 231Paxs/230Thxs would be useful coincide with locations which were maxima in the vertical particle flux during these periods. Reliable estimates of the North Atlantic mean 231Paxs/230Thxs should remain a goal in the longer term. Our results hint at a possible ‘‘seesaw-like’’ behavior in 231Pa/230Th in the South Atlantic.